A rapid dipstick test for serological diagnosis of brugian filariasis: evaluation results - N, Rahmah; H, Lokman; Anuar, Khairul; Hayati, Nor; M, Yazdanbakhsh; E, Sartono; TB, Nutman; RK, Shenoy; V, Kumaraswami; T, Supali; N, Weiss (2001)
A total of 753 serum samples from six institutions were used to evaluate an immunochromatographic rapid dipstick test (Brugia Rapid) for diagnosis of Brugia malayi infection.The samples comprised of sera from 207 microfilaria positive individuals and 546 individuals from filaria non-endemic areas.The latter consisted of 70 individuals with soil-transmitted helminthic infections, 68 individuals with other helminthic infections, 238 individuals with protozoan infections, 12 individuals with bacterial and viral infections and 158 healthy individuals. The dipstick is lined with goat anti-mouse antibody (control line) and a B. malayi recombinant antigen (test line).First, the dipstick is dipped into a well containing diluted patient sera, thus allowing specific anti-filarial antibody in the serum to react with the recombinant antigen.Then the dipstick is placed into an adjacent well containing reconstituted anti-human IgG4-gold.After 10 minutes, development of two red-purplish lines denotes a positive result and one line indicates a negative reaction. The overall results of the evaluation showed 91% sensitivity, 99% specificity, 97% positive predictive value and 99% negative predictive value. Brugia Rapid is thus a promising diagnostic tool for detection of B. malayi infection,and would be especially useful for the brugian filariasis elimination programme.